Modelling and sequential simulation of multi-tubular metallic membrane and techno-economics of a hydrogen production process employing thin-layer membrane reactor. (9th November 2016) - Shafiee, Alireza; Arab, Mobin; Lai, Zhiping; Liu, Zongwen; Abbas, Ali
Abstract: A theoretical model for multi-tubular palladium-based membrane is proposed in this paper and validated against experimental data for two different sized membrane modules that operate at high temperatures. The model is used in a sequential simulation format to describe and analyse pure hydrogen and hydrogen binary mixture separations, and then extended to simulate an industrial scale membrane unit. This model is used as a sub-routine within an ASPEN Plus model to simulate a membrane reactor in a steam reforming hydrogen production plant. A techno-economic analysis is then conducted using the validated model for a plant producing 300 TPD of hydrogen. The plant utilises a thin (2.5 μm) defect-free and selective layer (Pd75 Ag25 alloy) membrane reactor. The economic sensitivity analysis results show usefulness in finding the optimum operating condition that achieves minimum hydrogen production cost at break-even point. A hydrogen production cost of 1.98 $/kg is estimated while the cost of the thin-layer selective membrane is found to constitute 29% of total process capital cost. These results indicate the competiveness of this thin-layer membrane process against conventional methods of hydrogen production. Highlights: Theoretical model for multi-tubular palladium-based membrane at high temperatures. Sequential simulation for pure hydrogen and hydrogen binary mixture separations. Simulated membrane reactor in steam reforming 300 TPD hydrogen production plant. Plant utilises thin (2.5 μm) selective layer (Pd75 Ag25 alloy) membrane reactor. Competitive operating conditions identified at hydrogen production cost of $1.98/kg.